GaN Transistors for Efficient Power Conversion. - Lidow, Alex (Wiley, 2014)
The first edition of GaN Transistors for Efficient Power Conversion was self-published by EPC in 2012, and is currently the only other book to discuss GaN transistor technology and specific applications for the technology. More than 1,200 copies of the first edition have been sold through Amazon or distributed to selected university professors, students and potential customers, and a simplified Chinese translation is also available. The second edition has expanded emphasis on applications for GaN transistors and design considerations. This textbook provides technical and application-